2020
DOI: 10.1080/02646811.2020.1794108
|View full text |Cite
|
Sign up to set email alerts
|

What does energy security mean for energy-exporting countries? A closer look at the Russian energy security strategy

Abstract: This study offers a content analysis of the 2019 Energy Security Doctrine of Russia. The article demonstrates that the Russian energy security strategy is explicitly focused on the security of demand and acknowledges the threats caused by lowcarbon energy transition and economic sanctions. The Russian energy security strategy is clearly risk-centred, with explicitly different approaches to the management of internal and external risks to energy security. While domestic risks are associated with the security of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Such a policy, however, comes at the cost of deterioration or loss of energy security. This confirms the results of previous studies by Novikau (2021) and Proedrou (2022) on the Russian and Greek economies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Such a policy, however, comes at the cost of deterioration or loss of energy security. This confirms the results of previous studies by Novikau (2021) and Proedrou (2022) on the Russian and Greek economies.…”
Section: Discussionsupporting
confidence: 92%
“…The reason for this may be that the prioritization of energy security often takes place at the expense of giving up environmental goals, which is not a popular approach. This is also pointed out by Novikau (2021), who, analyzing the Russian energy strategy, concludes that the lowcarbon energy transition may pose a serious threat to energy security. Therefore, in the process of choosing energy carriers, Russia focuses on minimizing the risk of losing energy security by choosing those energy sources that it has control over, consciously giving up on maximizing environmental goals.…”
Section: Energy Policy Determinants and Energy Securitymentioning
confidence: 92%
“…In the case of analyzed countries, resource rents or composite energy security risk index do not play a role in their capacity to compete on international markets. This conclusion contradicts Novikau's [15] argument of the sole importance of energy demand security for exporters and energy supply security for importers. Adding to this, the results of previous research [7], in which authors found a positive relationship between energy supply security and export's competitiveness (among others: the USA and Norway), it may seem that for advanced energy exporters the idea of "energy competitiveness"-introduced by Zachmann and Cipollone [45]-is relevant.…”
Section: Discussionmentioning
confidence: 58%
“…Novikau [15,36], on the other hand, offered a more general approach to energy demand security. He argued that this idea includes "the availability of customers, price fairness, and energy transit security issues, such as control over pipelines".…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation